Réponses

Meilleure réponse !
2012-04-22T18:06:46+02:00

E= 3puissance5 /3puissance -4 fois (-2)puissance9

E= 3puissance9 fois (-2)puissance9

E= (-6)puissance9

 

F=10puissance5 / 2,5puissance -7 fois 4puissance -7

F=10puissance5 fois 4puissance -7 / 2,5puissance -7

F=10puissance5 fois (4/2,5)puissance -7

F=10puissance5 fois 1,6 puissance -7

F=10puissance5 fois (1/1,6) puissance 7

F=10puissance5 fois (0,625) puissance 7

F=10puissance5 fois (625 fois 10puissance-3) puissance 7

F=10puissance5 fois 625puissance 7 fois 10puissance-21

F=625puissance 7 fois 10puissance-16

F=37252902984619140625 fois 10puissance-16